Kinerja Keuangan sebagai Pemoderasi Faktor yang Mempengaruhi Nilai Perusahaan - Wadi Petra Juliani Zendrato; Marceline Vallery; Andreani Caroline Barus; Yola Yolanda (Jurnal Ilmiah METHONOMI, 2026)
The objective of this study is to analyze the effect of corporate governance specifically board structures and ownership types on firm valuation, with financial performance acting as a moderator. Focusing on 800 non-financial companies on the IDX from 2022 to 2023, 433 firms were selected using a purposive sampling technique. Data analysis via SmartPLS 3.2.9 reveals that among the governance variables, only independent commissioners significantly determine firm value. Other factors, such as board size and ownership distribution, show no substantial effect. Furthermore, financial performance only moderates the link between independent commissioners and firm value, while having no moderating impact on other governance-related variables.